Participatory action approach for client-centered health insurance - Fenenga, C.J.; Nketiah-Amponsah, E.; Bailey, A.; Hutter, I. (Action Research, 2015)
This methodological paper systematically describes the steps towards exploring client-perceived barriers to enroll in the National Health Insurance Scheme in Ghana. To respond to the stagnating enrollment rate and to provide evidence-based information for developing policy and practice, the request for this study was made by the insurance authority. We adopted a Participatory Action Approach (PAA) and employed a linked trajectory of qualitative and quantitative methods to inquire deeply into clients’ motives and assumptions, and the root causes of these barriers, while transferring learning among multiple stakeholders in the system: the client, the healthcare provider, and the insurer. Data were collected in 2011 and 2012 among clients in their local communities in two regions in Ghana. Clients were participants in the research, expressing and sharing their emic perspectives and commonly shared opinions with the other stakeholders. This paper explores the contribution of the PAA to healthcare and health insurance studies. We claim that the PAA is a necessary approach for the study of a complex situation such as the health insurance context in Ghana as well as for the facilitation of learning and democratic decision-making. Making multidisciplinary stakeholders, including clients, part of the research contributes to finding solutions that are acceptable to different stakeholders. Our study contributes to PAA methodology knowledge and provides new insights on combining qualitative and quantitative research methods. We propose this as a model to be used within action research that can also be applied in other contexts outside of Africa.
Keywords: Participatory Action Approach; clients; perceptions; health care; health insurance; policy development; Ghana